1996
DOI: 10.1093/oxfordjournals.aje.a008958
|View full text |Cite
|
Sign up to set email alerts
|

Association between Use of Spermicide-coated Condoms and Escherichia coli Urinary Tract infection in Young Women

Abstract: Diaphragm/spermicide use increases the risk of urinary tract infection (UTI). To determine whether spermicide-coated condoms are also associated with an increased risk of UTI, the authors conducted a case-control study at a large health maintenance organization in Seattle, Washington. Cases were sexually active young women with acute UTI caused by Escherichia coli, identified from computerized laboratory files during 1990-1993. Age-matched controls were randomly selected from the enrollment files of the plan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 18 publications
(22 reference statements)
4
38
0
2
Order By: Relevance
“…Earlier case-control studies in young women without diabetes have demonstrated that sexual intercourse and diaphragm/spermicide or condom use are significantly associated with the presence of UTIs (12,13). A large prospective study of sexually active young women also showed that recent sexual intercourse and the use of diaphragms with spermicide were strong risk factors for UTI development (14).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier case-control studies in young women without diabetes have demonstrated that sexual intercourse and diaphragm/spermicide or condom use are significantly associated with the presence of UTIs (12,13). A large prospective study of sexually active young women also showed that recent sexual intercourse and the use of diaphragms with spermicide were strong risk factors for UTI development (14).…”
Section: Discussionmentioning
confidence: 99%
“…The use of spermicides and condoms may irritate and traumatise the tissues during sexual activity. 13 Thus, increasing the risk of bacterial invasion of the affected and surrounding tissues. Switching to lubricated condoms without spermicide or using a nonspermicidal lubricant may help prevent UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these studies, it seems likely that the antimicrobial activity of spermicides alters the vaginal ecosystem and provides a suitable environment for growth and proliferation of uropathogens. It is interesting to note that small amounts of nonoxynol-9 on condoms can increase the risk of UTI in females in the absence of sexual intercourse (Fihn et al 1998, Fihn et al 1996.…”
Section: Spermicidal Compoundsmentioning
confidence: 99%